Kontribusi Kekuatan Otot Lengan, Koordinasi Mata Tangan Dan Kekuatan Otot Perut Pada Kemampuan Servis Atas Bolavoli Pada Siswa UPT SPF SMP Negeri 29 Bulukumba - Milda Karmila; Hasbunallah As; M. Adam Mappaompo; Muh. Adnan Hudain; Benny B (Journal on Education, 2024)
This research is quantitative descriptive research with aims 1). To determine the contribution of arm muscle strength to volleyball serving ability, 2). To determine the contribution of hand-eye coordination to volleyball serving ability. 3). To determine the contribution of abdominal muscle strength to volleyball serving ability. 4) To find out together the strength of the arm muscles, eye hand coordination and abdominal muscle strength on the ability to serve in volleyball among UPT SPF students at Bulukumba State Middle School. The independent variables in this study were arm muscle strength, hand eye coordination, and abdominal muscle strength, while the dependent variable was upper serve ability. The population in this study was all students in class VII-VIII UPT SPF SMP Negeri 29 Bulukumba totaling 60 students with 30 male students used as samples using a probability sampling technique (random sampling). The data collection techniques used were giving arm muscle strength tests (push ups), hand eye coordination tests (throwing and catching ball tests), and abdominal muscle strength tests (sit-ups), observation and documentation. Descriptive data analysis techniques and inferential statistical analysis using correlation and regression tests. The results of correlation and regression tests related to the contribution of arm muscle strength to the ability to serve in volleyball showed R2= 0.756 (P=0.000), the contribution of eye and hand coordination to the ability to serve in volleyball showed R2= 0.684 (P=0.000), the contribution of abdominal muscle strength to volleyball service ability shows R2= 0.534 (P=0.000) and the integrated contribution of arm muscle strength, abdominal muscle strength, and hand eye coordination to volleyball service ability shows R2= 0807 (P=0.000). So it can be concluded that arm strength, hand-eye coordination, and abdominal muscle strength each have a linear contribution to the volleyball serving ability of UPT SPF students at SMP Negeri 29 Bulukumba. And there is a significant contribution from the combination of arm muscle strength, hand eye coordination and abdominal muscle strength to the volleyball service ability of UPT SPF students at SMP Negeri 29 Bulukumba.